GENERAL SCIENTIFIC RESEARCH METHODS (KONFERENSIYA, 2026)
General scientific research methods are fundamental tools used across various disciplines to systematically investigate phenomena, gather data, and generate knowledge. These methods provide structured approaches to formulating research questions, designing experiments, collecting and analyzing data, and drawing valid conclusions. The use of rigorous research methodologies ensures objectivity, reliability, and reproducibility of scientific findings. This paper explores the key types of general scientific research methods, including qualitative and quantitative techniques, experimental and observational approaches, as well as the importance of selecting appropriate methods based on research goals. Understanding these methods is essential for researchers to effectively address complex problems, contribute to the advancement of science, and apply findings in practical contexts.